Reducing the uncertainty in the distribution of cm-scale rock properties in the near well-bore region - Seyed Ahmad Mortazavi; Seyed Ahmad Mortazavi; Achyut Mishra; Achyut Mishra; Julie Dickinson; Julie Dickinson; Ralf R. Haese; Ralf R. Haese (Frontiers in Earth Science)
Rock properties at cm-scale impact geological carbon storage by enhancing capillary and mineral trapping. Hence, it is important to accurately capture their distribution in geo-models which are used for numerically estimating the fate of injected CO2. However, there could be high variability in the cm-scale distribution of rock properties even close to wells which is not captured with traditional workflows. This study explores the impact of grid cell resolution, seismic inversion and placement of an additional well in proximity to CO2 injection well on improving the representation of cm-scale lithological heterogeneity in the near well bore region in geological models. We utilize wireline and seismic data from Parasequence-2 of the Paaratte Formation, Otway Basin, Australia, which is a shallow to coastal marine deltaic deposition comprising a high degree of lithological heterogeneity and a prospective unit for pilot scale geological carbon storage operations. The data was used to prepare a suite of reservoir models capturing the impact of above factors on the plausible distributions of facies, porosity and permeability in the formation. The analysis suggests that smaller grid cell size (1 m × 1 m × 0.3 m) compared to the typical industry standard (10 m × 10 m × 2 m) significantly improves the representation of cm-scale rock properties. Additionally, stochastic seismic inversion could play an important role in capturing rock property distribution even for smaller CO2 storage sites used for pilot scale injection operations. Further, we show that the placement of an additional well only 116-m away from the CO2 injection well can drastically improve the probability in the distribution of cm-scale rock properties in reservoir models.